Effects of the Latex of Synadenium grantii Hook F. (Euphorbiaceae) on a Preclinical Model of Canine Prostate Cancer - Brito, Eric Saymom Andrade; Prado, Laís Di Paulie Taborda; Araújo, Liana Késia Costa; Arnhold, Emmanuel; Matos, Moema Pacheco Chediak; de Paula, Joelma Abadia Marciano; Ramos, Luciana Machado; Fonseca-Alves, Carlos Eduardo; de Moura, Veridiana Maria Brianezi Dignani (Frontiers in Veterinary Science, 2021)
Prostatic cancer (PC) stands out in terms of its occurrence, pathophysiology, and unfavorable prognostics in humans and dogs. Natural drugs bear an integrative potential for conventional antineoplastic treatments. In this context, the bioproducts of Synadenium grantii have been empirically used in different parts of Brazil for the integrative treatment of prostate cancer in humans. However, there is no availability of scientific evidence of the antitumor effects of S. grantii. Therefore, this study aimed to investigate the bioactive compounds in the latex of S. grantii using the high-resolution mass spectrophotometry (HRMS) and to evaluate its cytotoxic effects on primary canine PC cell cultures. Four fragments of phorbol ester were identified as potential bioactive compounds using the HRMS. With the help of an MTT ([3-(4,5-dimethyldiazol-2-yl)-2,5 diphenyltetrazolium bromide]) assay, two canine prostatic carcinoma cell lines (PC 1 and PC2) showed a decrease in the tumor cell count, with an Inhibitory concentration 50 (IC50)of 0.8469 and 0.6068 mg/ml, respectively, for PC1 and PC2. In conclusion, the latex of S. grantii contains phorbol esters in its composition, and its aqueous solution has a cytotoxic effect on canine metastatic PC cells in vitro.